2016
DOI: 10.1016/j.jcv.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Human metapneumovirus in patients hospitalized with acute respiratory infections: A meta-analysis

Abstract: This meta-analysis aimed to estimate the prevalence of human metapneumovirus (hMPV) infections in patients hospitalized for acute respiratory infection (ARI) and to study factors associated with this prevalence. Medline and ScienceDirect databases were searched for prospective observational studies that screened hospitalized patients with ARI for hMPV by RT-PCR, with data available at December 27, 2014. The risk of bias was assessed regarding participation rate, definition of ARI, description of diagnostic tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 100 publications
2
17
2
1
Order By: Relevance
“…Prior analyses have shown that influenza is the most common cause of ILI during the influenza season, accounting for 50-70% of such cases [22,23], whereas RSV and hMPV infections account for 3-6% of cases in previously healthy individuals [24,25]. In contrast, RSV and hMPV infections can be detected in 16-25% of hospitalized adults ≥ 65 years old with chronic medical conditions [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Prior analyses have shown that influenza is the most common cause of ILI during the influenza season, accounting for 50-70% of such cases [22,23], whereas RSV and hMPV infections account for 3-6% of cases in previously healthy individuals [24,25]. In contrast, RSV and hMPV infections can be detected in 16-25% of hospitalized adults ≥ 65 years old with chronic medical conditions [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Two investigators evaluated risk of bias in included studies using an eight‐item rating scale . These items included (a) participation response rate more than 75% agree to participate or analysis to show whether respondents and nonrespondents were similar for the sociodemographic characteristics; (b) ARTI clearly defined; (c) method of inclusion identical for all subjects; (d) description of diagnostic technique; (e) same type of sample collected for all patients (nasopharyngeal aspirate, nasal, or throat swab); (f) standardized method for sample collection (quantity of aspirate or of liquid used for the nasal wash with any virological medium transport for swabs); (g) analysis performed according to relevant subgroups (by age classes, by center, or by symptomatology, for example); and (h) and presentation of data sources (counts are presented, not only percentages).…”
Section: Methodsmentioning
confidence: 99%
“…Prior analyses have shown that in uenza is the most common cause of ILI during in uenza season, accounting for 50-70% of such cases [22][23], whereas RSV and hMPV infections account for 3-6% of cases in previously healthy individuals [24][25]. In contrast, RSV and hMPV infections can be detected in 16-25% of hospitalized adults ≥ 65 years old with chronic medical conditions [26][27].…”
Section: Discussionmentioning
confidence: 99%